Relationship of Mother Knowledge About Eruption and Caries of M1 Permanent Teeth at SDN 05 Bukittinggi 2017 - Yustina Srinai; Aljufri Aljufri; Normasari Pane (Jurnal Kesehatan Masyarakat Andalas, 2017)
The permanent first molars teeth are susceptible to caries after eruption. According to parents, the teeth still has suffering, and they do not notice it. In research at 2012 said the children 9 years old had a high permanent molar caries teeth with percentage of 67%. This study aims to determine the relationship of mother knowledge abouteruption of M1 permanent teeth with M1 caries at SDN 05 PuhunPintuKabundistrict of Bukittinggi. This research used Analytical survey method with cross sectional design. The research population of all students of SDN 05 PuhunPintuKabunfor amount 120 students. The sample is saturated sampling that is the whole population used as the respondent with permanent dental calculation and eruption and present time of research. Data were collected by examination of single student molar caries and filling in questionnaire by mother. Data analysis using chi square test. The results of this research that the most knowledge of mother’s knowledge on the less appetizing is 58%, and good knowledge 9%. Number of students given permanent M1 of 51% and 49% do not caries. Chi square statistic test P value: 0.565 (p> 0.05) means that there is no correlation between knowledge about permanent M1 eruption with M1caries. It is advisable to students who have permanent M1 to perform dental fillings.